A Note on the GMRES Method for Linear Discrete Ill-Posed Problems (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we are presenting a proposal for new modifiedalgorithms for RRGMRES and AGMRES. It is known that RRGMRES andAGMRES are viable methods for solving linear discrete ill-posedproblems. In this paper we have focused on the residual norm andhave come up with two improvements where successive updates and thestabilization of decreases for the residual norm improve performancerespectively. Our numerical experiments confirm that our improvedalgorithms are effective for linear discrete ill-posed problems.